The social-ecological landscape of herding on the high mountain commons of Larrau in the western Pyrenees (France) - Gragson, Ted L; Coughlan, Michael R. (Frontiers in Human Dynamics, 2024)
Much has been written about herding, pastoralism and the ethos of the commons that persists in Soule and the valley republics of the Western Pyrenees. However, more has been written about the idealized norms of the practice than the social dynamics of alliance formation on which cooperation in herding on the high mountain commons has for centuries depended in Soule. A Cayolar is a syndicate of herders associated with a named inholding within the high mountain commons. It lies within a class of pastoral institutions found across the western Pyrenees with features particular to pastoral institutions of mountain herders elsewhere in Europe. Empirical evidence from the parish-commune of Larrau containing most of the common high rangelands in Soule are used to analyze the emergence, social alliance, and landscape placement of Cayolar. Results are then put in the context of regional forces across the Middle Ages shaping the collective action of herders in the Soule Valley.